Mimicking Adhesion in Minimal Synthetic Cells. Issue 6 (25th February 2019) - Bartelt, Solveig M.; Chervyachkova, Elizaveta; Ricken, Julia; Wegner, Seraphine V.
Abstract: Cell adhesions to the extracellular matrix and to neighboring cells are fundamental to cell behavior and have also been implemented into minimal synthetic cells, which are assembled from molecular building blocks from the bottom‐up. Investigating adhesion in cell mimetic models with reduced complexity provides a better understanding of biochemical and biophysical concepts underlying the cell adhesion machinery. In return, implementing cell–matrix and cell–cell adhesions into minimal synthetic cells allows reconstructing cell functions associated with cell adhesions including cell motility, multicellular prototissues, fusion of vesicles, and the self‐sorting of different cell types. Cell adhesions have been mimicked using both the native cell receptors and reductionist mimetics providing a variety of specific, reversible, dynamic, and spatiotemporally controlled interactions. This review gives an overview of different minimal adhesion modules integrated into different minimal synthetic cells drawing inspiration from cell and colloidal science. Abstract : Implementing cell adhesions to the matrix and to neighboring cells into minimal synthetic cells provides reductionists models for understanding the biochemical and biophysical principles behind cell adhesions. Furthermore, reconstructing mimetic cell adhesions that mirror the reversible, dynamic, and spatiotemporal control found in natural cell adhesions allow to rebuild adhesion dependent cellular functions like cell motility, prototissues, fusion, and self‐sorting.